2020
DOI: 10.1126/science.aba9475
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating scenarios toward zero plastic pollution

Abstract: Plastic pollution is a pervasive and growing problem. To estimate the effectiveness of interventions to reduce plastic pollution, we modeled stocks and flows of municipal solid waste and four sources of microplastics through the global plastic system for five scenarios between 2016 and 2040. Implementing all feasible interventions reduced plastic pollution by 40% from 2016 rates and 78% relative to ‘business as usual’ in 2040. Even with immediate and concerted action, 710 million metric tons of plastic waste c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
616
2
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 1,049 publications
(647 citation statements)
references
References 86 publications
9
616
2
20
Order By: Relevance
“…technical nutrients, and even some biological ones) that leak to the environment may take years to degrade (e.g. plastics and bio-based alternatives), and as a result, they can cause serious harm to ecosystems and human health (Awasthi et al 2019;Lau et al 2020). Currently, there is a lack of consensus on what constitutes a source (i.e.…”
Section: Natural Environment and Provisioning Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…technical nutrients, and even some biological ones) that leak to the environment may take years to degrade (e.g. plastics and bio-based alternatives), and as a result, they can cause serious harm to ecosystems and human health (Awasthi et al 2019;Lau et al 2020). Currently, there is a lack of consensus on what constitutes a source (i.e.…”
Section: Natural Environment and Provisioning Servicesmentioning
confidence: 99%
“…Waste resources are rarely monitored once they cross borders, and as a result, their fate remains unknown. Yet, developed countries account the exported waste resources in their recycling estimations (and thus, circularity targets), whilst it is very likely that these wastes may be mismanaged (i.e., inadequately disposed and littered) contributing to negative value creation elsewhere with often deleterious impacts on ecosystems and human health (Huang et al 2014;Iacovidou et al 2020b;Lau et al 2020). Foreign recyclable waste markets in developing countries tend to have a questionable waste infrastructure and often weaker, less reliable institutions to control the management of waste (Dauvergne 2018;Osibanjo and Nnorom 2007;Schmidt 2006).…”
Section: Natural Environment and Provisioning Servicesmentioning
confidence: 99%
“…For instance, the 2017 cleanup event showed that the dominated top items collected around the global based on item counts of coastal litter were all made of plastics, which was repeated during the 2018 cleanup event [20]. Meanwhile, a number of studies provide estimates of marine plastic debris [4,21]. As recently reported by Eriksen et al [22], an estimated figure of the volume of plastics floating in the oceans, and found that more than five trillion pieces of plastic and approximately 268,940 tons are currently floating in the oceans.…”
Section: Mpp: Sources Pathways and Estimationmentioning
confidence: 99%
“…The topic of solid waste mismanagement has attracted considerable attention in recent years, not least because of the large quantities of plastic waste that are reported to enter the aquatic environment (11 million metric tons per annum Mt y -1 ), mainly in the low-and middleincome countries (LIMICs) of South and Southeast Asia. 1 Our high dependence on plastics in almost every aspect of life has resulted in an exponential growth curve for plastic production since the 1950s, anticipated to continue unabated until 2050. 2 Underlying this growth in plastic production, is the rapidly rising population that is projected for several middle-income countries in the Global South, 3 where newly attained prosperity is allowing their citizens to benefit from the properties and characteristics that plastics bring to their lives such as freshness of food, fuel economy of transport systems, and insulating properties in constructions.…”
Section: Introductionmentioning
confidence: 99%
“…are combusted in open, uncontrolled fires (49 Mt y -1 ). 1 For the 2 billion inhabitants of earth that have no solid waste collection, 8 open burning is an effective self-management approach that quickly reduces the mass (up to 75% wt.) and volume (up to 90% v/v.)…”
Section: Introductionmentioning
confidence: 99%